The Paranormal and the Politics of Truth : a Sociological Account. - Northcote, Jeremy (Andrews UK, 2013)
This book is based on the author's ten-year research into the politics of belief surrounding paranormal ideas. Through a detailed examination of the participants, issues, strategies and underlying factors that constitute the contemporary paranormal debate, the book explores the struggle surrounding the status of paranormal phenomena. It examines, on the one hand, how the principal arbiters of religious and scientific truths - the Church and the academic establishment - reject paranormal idea ...